Scope and limitations of nuclear magnetic resonance techniques for characterisation and quantitation of vitamin D in complex mixtures. Issue 1 (24th September 2019) - Robertson, Cameron; Lucas, Robert A.; Le Gresley, Adam
Abstract: Background: The accurate determination of vitamin D in skin is of considerable importance in evaluating penetration of skin health products through the different layers of the skin. Objective: We report on the characterisation and quantitation of vitamin D in an idealised sample and in complex mixtures which mimic that of a typical skin cream, using qNMR, 2D NMR and DOSY techniques. Methods: The characterisation and quantitation conditions were acquired over several heterogeneous samples, allowing for analysis of how the dynamic range and complexity of the different sample mixtures affect the limits of detection (LOD) and limits of quantitation (LOQ) of vitamin D. NMR is of particular value to this task as it is non‐destructive, uses a primary ratio method for quantification, and tolerates a wide variety of hydrophilic and hydrophobic components within a given matrix. Results: In this investigation, we have attained a trueness level <10%, repeatability values of <1% and brought the limit of quantitation down to 100 nmol/L (≈limit of baseline range of vitamin D2 and D3 per litre seen in vivo), commenting on the limitations observed, such as peak overlap and sensitivity limits. Conclusions: Pure shift optimised sequences allow us to reduce peak overlapping, allowing further characterisation of individual compounds and the separation of complex mixtures using NMR.